2017
DOI: 10.1111/inr.12371
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for obesity in preschool‐aged children in China

Abstract: Understanding factors associated with childhood obesity can assist researchers and clinicians to develop culturally sensitive and evidence-based programmes and policy to reduce this global epidemic.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 30 publications
0
15
0
Order By: Relevance
“…A study by Chen et al. () also reported that maternal belief about their child's risk for obesity is associated with higher child BMI. Existing literature states that parents who accurately perceive their child's weight are more likely to be motivated to change their health‐related behaviours (Kaufman‐Shriqui et al.…”
Section: Discussionmentioning
confidence: 95%
See 3 more Smart Citations
“…A study by Chen et al. () also reported that maternal belief about their child's risk for obesity is associated with higher child BMI. Existing literature states that parents who accurately perceive their child's weight are more likely to be motivated to change their health‐related behaviours (Kaufman‐Shriqui et al.…”
Section: Discussionmentioning
confidence: 95%
“…Children whose parents perceived their child as overweight/obese had higher BMI z-scores than those with parents who perceived their child's weight as normal. A study by Chen et al (2017) also reported that maternal belief about their child's risk for obesity is associated with higher child BMI. Existing literature states that parents who accurately perceive their child's weight are more likely to be motivated to change their health-related behaviours (Kaufman-Shriqui et al 2012;Mareno 2014).…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Children at this age have not yet formed a personal pattern of health-related habits or preferences, which means that they are most likely to be affected by a nurturing environment (Lee, Park, & Lee, 2018). Particularly, the parenting or behavior of a mother who is a primary caregiver correlates significantly with childhood obesity; thus, a strategy where mothers are included in the intervention is relevant (Chen, Esquivel, Guo, Chesla, & Tang, 2018).…”
Section: Introductionmentioning
confidence: 99%